What's mine is yours the ethics of big data ownership - Field, Dylan; O'Reilly, Tim.; Goldberg, Nolan; Valeski, Jud.; Fitzpatrick, Brian .; Safari eBooks; O'Reilly strata making data work conference (2011 : (dollar)c Santa Clara, Calif.) ([Sebastopol, Calif.?] : O'Reilly Media, 2011)
"To many people, Big Data means Open Data: social graphs, voting records, weather patterns, and more. But who owns data? Most of our laws were written for atoms, not bits; they're woefully out of date in an information age. When you share data, does it become more or less valuable? If someone adds to your data, is it still yours? This panel will tackle the gray area of data ownership."--Resource description page.
Title from title screen.
Interviewer, Dylan Field.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, CA.
Keywords: Privacy, Right of; Data protection; Freedom of information; Database management; Electronic books